Pengembangan Media Prezi pada Pembelajaran Menulis Cerita Pendek Siswa Kelas XI SMA se-Kota Tangerang di Era Digital - Winda Dwi Hudhana; Hamdah Siti Hamsanah Fitriani (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to explain the results of Prezi's media development in learning to write short stories for XI grade high school students in Tangerang City in the digital era. The method in this research is a development research methodology with steps namely field observation, research planning and design, product development, product validation, product revision, field testing, revision of field trials, and implementation of learning media. Data collection techniques using tests and questionnaires. The research instrument was through questionnaires and tests. Data analysis techniques using data trend techniques. The validity test was carried out on 5 Prezi media experts and 5 short story material experts. The results showed that the Prezi media was feasible and effective to be implemented in the learning of the XI grade high school students 'short stories because the Prezi media was easy to make by the teacher, Prezi's appearance attracted students' attention more, the teacher could create learning media according to the teacher's creativity and was easily understood by students. Based on the results of the validation of the five Prezi media experts, an average of 85.2% was categorized as feasible. The validation of five learning experts to write short stories obtained an average score of 86.8% with a decent category. The results of the Prezi media trial on learning to write short stories obtained an average score of 78.6. The use of Prezi media products in learning to write short stories obtained an average score of 78 out of 30 students. The implementation of Prezi media products in learning to write short stories obtained an average score of 73 out of 30 students. The implementation of Prezi media products in learning to write short stories obtained an average score of 65.5 from 20 students.